Wire bristle foreign body: Never in the same place twice - Andrew DP Prince; Ashley M Bauer; Yanjun Xie; Mark EP Prince (SAGE Open Medical Case Reports, 2019)
Foreign body ingestion is a common reason for visiting the emergency room. Foreign bodies can lodge anywhere in the upper aerodigestive tract and can sometimes be difficult to extract. Wire bristles that dislodge from grill-cleaning wire brushes and which are then accidentally swallowed can be particularly challenging to remove due to their small size, propensity to become embedded, and their ability to migrate through tissues. This case reveals the speed with which wire bristle foreign bodies can migrate through tissues and exemplifies the need to obtain computerized tomography evaluations in close proximity to any planned attempt to remove them.